(untitled) (Journal of Legal Studies, 2019)
One of the forms that cybercrime can take at present is illegal access to a computer system. From the very beginning, the world of computers and of the Internet was based on imperfections, defects, and sometimes on poorly understood processes. We might even call this fact ―the original sin‖ of the Internet. In the end, it is not only computer scientists who have come to exploit such defects, but also criminals. In the real world, there are people who break into homes and take away everything they find valuable. In the virtual world, there are individuals who penetrate into computer systems and steal all valuable data.